M2M Communication in Virtual Sensor Network for SHAAL - Zubair, Khalid; N., Fisal; Rahat, Ullah; Hashim, Safdar; Wajaha, Maqbool; S., Zubaira; Adnan, Shahid Khan (UTM Press, 2012)
Machine-to-Machine (M2M) communication has led to a new paradigm of Internet of Things (IoT). The future of M2M communication in smart home lies in the aggregation and allocation of resources and service provisioning of diverse applications using different radio technologies. M2M communication may operate on the virtual sensor network to provide independent applications running on heterogeneous network simultaneously. M2M is going to play a major role in the area of Smart Home and Ambient Assisted Living (SHAAL) providing assistance to the elderly people with smart sensors that monitor the home environment and provides aid health monitoring to human requiring medical assistance. The current state of the art frameworks are dedicated to specific applications with the support of single radio network with limited service provisioning options. However, in order to fully exploit the resources in this paper we present a service provisioning framework realization of M2M in virtual sensor network for SHAAL, which allows independent parties to work together in a secure and reliable manner. In addition to this, the framework is designed to include benefits of Service Oriented Architecture (SOA) and Resource Oriented Architecture (ROA) along with the use of different low power, low data rate protocols. A middleware is used as a platform to link the underlying virtual networks with various applications. The network virtualization approach is adopted to design an efficient middleware framework that can effectively discover and manage the underlying network resources and provide services at home gateway. The framework will be used as the basis for the development of the SHAAL networked system.